2017
DOI: 10.1038/oncsis.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

ASCT2 regulates glutamine uptake and cell growth in endometrial carcinoma

Abstract: Glutamine commonly becomes a conditionally essential amino acid in cancer. Glutamine is supplied to the cell by transporters such as ASCT2 (SLC1A5), which is frequently upregulated in multiple cancers. Here we investigated the expression of ASCT2 in endometrial carcinoma, and evaluated the contribution of ASCT2 to glutamine uptake and endometrial cancer cell growth. Analysis of human gene expression data showed that ASCT2 was significantly upregulated in both endometrioid and serous subtypes of endometrial car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…A pooled analysis of individual-level data from 10 cohort and 14 case-control studies identified that patients with these 2 endometrial cancer types shared a number of common etiologic factors, including parity, oral contraceptive use, cigarette smoking, age at menarche and presence of diabetes (24). Furthermore, shared molecular regulatory mechanisms among these 2 pathological subtypes of Ec have been previously reported, such as solute carrier family 1 member 5 regulating glutamine uptake and cell growth in Ec (25). In the present study, the differences in methylation status and expression levels of miR-638, as well as expression levels of MEF2C, were compared among cancerous tissues and non-cancerous tissues in clinical samples from patients with endometrioid adenocarcinoma and serous carcinoma.…”
Section: Discussionmentioning
confidence: 95%
“…A pooled analysis of individual-level data from 10 cohort and 14 case-control studies identified that patients with these 2 endometrial cancer types shared a number of common etiologic factors, including parity, oral contraceptive use, cigarette smoking, age at menarche and presence of diabetes (24). Furthermore, shared molecular regulatory mechanisms among these 2 pathological subtypes of Ec have been previously reported, such as solute carrier family 1 member 5 regulating glutamine uptake and cell growth in Ec (25). In the present study, the differences in methylation status and expression levels of miR-638, as well as expression levels of MEF2C, were compared among cancerous tissues and non-cancerous tissues in clinical samples from patients with endometrioid adenocarcinoma and serous carcinoma.…”
Section: Discussionmentioning
confidence: 95%
“…However, glutamine, a conditionally essential amino acid that is the most commonly depleted amino acid in solid tumors, can serve as a carbon source for the TCA cycle and as a nitrogen source for nucleotide biosynthesis (44). Like glucose, amino acids cannot cross the lipid bilayer without transporter proteins, and amino acid transporter expression is positively correlated with growth and cancer (45). We found the expression levels of glutamine transporters and glutaminase in CWR22RV1 and C4-2B cells are potentiated by glu-aggressive differentiation state.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 10 6 HeLa cells in PBS were fixed in 70% ethanol for at least 2 hrs on ice. After fixation step, cells were pelleted and washed with PBS before suspending cells with staining solution containing 20 µg/ml of PI, 0.1% of Triton X-100 and 0.2 mg/ml of DNase-free RNase A in PBS for 15 min at 37 degree.…”
Section: Methodsmentioning
confidence: 99%
“…There have been significant efforts to pharmacologically target ASCT2 for the inhibition of cancer cell growth. For example, monoclonal antibodies against ASCT2 or chemical ASCT2 inhibitors, such as benzylserine and gammal-Glutamyl-p-nitroanilide (GPNA), have been shown to inhibit cell growth of various cancers (5)(6)(7). While the impact of cell proliferation through ASCT2 activity is clear, the molecular details of how ASCT2 activity is regulated are poorly understood.…”
mentioning
confidence: 99%